Trade, labour and sustainable development: an integrated perspective - Khan, Zobaida (McGill University, 2017)
Some contemporary challenges for global trade regulation and labour governance arise from the barriers between questions of law and social justice, and development policy and distributional issues. This thesis attempts to address some of these regulatory or governance challenges by exploring the interactions between sustainable development (SD), trade regulation, and social or distributive justice. Borrowing from multiple disciplines, i.e. law, international relations, and development economy, and focusing on the problems of low-income countries, this thesis examines the potential and importance of a broad ideational objective in introducing transformative changes in different regulatory or governance mechanisms. This thesis does not discuss ways to link trade regulation or labour governance with SD; rather here the possibilities of operationalizing SD, within the global trade regulatory site or transnational governance mechanisms, are explored from a capability perspective. It is argued that a capability-based understanding can resituate some questions on trade-SD interaction and introduce important behavioural changes in the functioning of the World Trade Organization (WTO). Yet, ongoing operationalization of capability-based SD requires effective market complementary interventions from governance mechanisms operating at different spaces and with diverse actors. Certain emerging transnational governance mechanisms, which connect broader social or distributional issues such as labour governance with trade opening or economic cooperation, attempt to provide crucial market complementary interventions. Taking examples from the recent transnational safety initiatives for Bangladeshi garment workers and relying on a broad conceptualization of the social or distributional issues, it is argued that attention to capability enhancement produces a much more compelling form of labour governance mechanism at these hybrid sites. With a focus on capability-based SD, a model of transformative linkage is proposed for effective labour governance. The model demands that fundamental and redistributive rights of labour are interconnected and appropriate labour governance requires a stronger form of corporate responsibility. Analyzing the interaction of diverse rules, governance processes and mechanisms, with the demands of marginalized forces the global hegemony of capital is juxtaposed with available options and possible alternatives.
Keywords: Corporate Social Responsibility; Labour; Social justice; Sustainable development; Trade regulation

The international legal framework on business and human rights and its domestic operationalisation : strategic litigation on mining and a healthy environment in South-Africa - Verdonck, Lieselot (Ghent University, 2017)
The debate on business and human rights attracts the interest of many parties, and regularly makes the headlines. On 19 January 2017 De Morgen, for instance, ran the following headline: “These banks do business with companies that violate human rights and nature”. The discourse suggests that few question that business enterprises should respect human rights. The legal meaning and consequences of associating 'business' with 'human rights' remain contentious, however. By clarifying the existing legal framework this thesis seeks to rationalize the debate. Special attention is paid to enforcing the responsibility of business enterprises for human rights through domestic judicial remedies. The analysis is concretised through a case study on adverse human rights impacts of environmental degradation caused by mining in South Africa. Based on the findings of the study, the thesis reflects on how the international legal framework on business and human rights should be developed further.
Keywords: Business; CSR; CSR disclosure; Human rights; International law; RSE; South Africa